Plasma oxytocin concentrations are lower in depressed vs. healthy control women and are independent of cortisol - Yuen, Kaeli W. (J Psychiatr Res, 2013)
The neuropeptide oxytocin (OT) promotes social behavior and attenuates stress responsivity in mammals. Recent clinical evidence suggests OT concentrations may be dysregulated in major depression. This study extends previous research by testing whether: 1) OT concentrations vary systematically in depressive disorders with and without hypercortisolemia, 2) gender differences in OT concentrations are observed in depressed vs. healthy control participants, and 3) OT concentrations are predictive of clinical phenotypes. Plasma OT concentrations of psychotic major depressive (PMD; n = 14: 10 female, 4 male), non-psychotic major depressive (NPMD; n = 17: 12 female, 5 male), and non-depressed, healthy control (n = 19: 11 female, 8 male) participants were assayed at 2000, 2400, 0400, and 0800 h. Plasma cortisol concentrations were quantified at 2300 h, and clinical phenotypes were determined. As expected, PMD participants, compared to NPMD and healthy control participants, showed higher plasma cortisol concentrations. Although both depressed groups showed similar OT concentrations, a significant interaction effect between group and gender was observed. Specifically, depressed females exhibited lower mean OT concentrations than depressed males. Further, depressed vs. healthy control female participants exhibited lower mean OT concentrations, whereas depressed vs. healthy control male participants showed a trend in the opposite direction. OT concentrations were also predictive of desirability, drug dependence, and compulsivity scores as measured by the Million Clinical Multiaxial Inventory-III. All findings were independent of cortisol. These data suggest that OT signaling may provide a mechanism by which to better understand female-biased risk to develop depressive disorders and that plasma OT concentrations may be a useful biomarker of certain clinical phenotypes.